Contested subjectivities in a UK housing cooperative: old hippies and Thatcher's children negotiating the commons. Issue 110 (March 2020) - Arbell, Yael; Middlemiss, Lucie; Chatterton, Paul
Highlights: Multiple and contested subjectivities underpin different visions for the commons. Visions for the commons are diverse and may be minimalist or maximalist. Older and long-term members were more maximalist than younger members. Over 40 years, a housing cooperative shifted towards a minimalist vision. Neoliberalisation was seen as a reason for changing visions and subjectivities. Abstract: How can a long-standing cooperative respond to changes in society over time, and how do these changes affect the management of the cooperative? We looked at the visions, daily life and policies in a housing cooperative in the UK established in the 1970s and found a messy process that required constant negotiation and involved diverse subjectivities. We identified different visions of the commons: a minimalist vision focusing on housing alone, and a maximalist one, diffusing boundaries between the personal and the collective and involving many aspects of members' lives. These visions have always existed in the cooperative, but the general trend was towards minimalism. Behind the changes are members' changing subjectivities, reflecting changing processes of subject formation in relation to state and market. We found that difference in subjectivities was often displayed along generational lines, and affected commoners' visions of the commons. Although the cooperative changed some of its practices to fit the more minimalist vision, it still endured as a form of commons that is resilient to challenge.